The Patient Safety Screener: Validation of a Brief Suicide Risk Screener for Emergency Department Settings. Issue 1 (2nd January 2017) - Boudreaux, Edwin D.; Jaques, Michelle L.; Brady, Kaitlyn M.; Matson, Adam; Allen, Michael H.
Abstract : This study evaluated the concurrent validity of a brief suicide risk screener for adults in the emergency department (ED). Two versions of the verbally administered Patient Safety Screener (2-item, 3-item) were compared to a reference standard, the Beck Scale for Suicide Ideation (BSSI). Analyses included measures of agreement (Kappa). Agreement between the Patient Safety Screener-2 and -3 and the BSSI (n = 951) was almost perfect for overall positive screening (K = 0.94–0.95) and past suicide attempts (K = 0.97–0.98). Agreement on ideation ranged from fair (K = 0.34) for the 2 item version to good (K = 0.61) for the 3 item version. The Patient Safety Screener's concurrent validity with the BSSI ranged from fair to almost perfect and warrants additional study.